Race Questions, Provincialism, and Other American Problems : Expanded Edition - Royce, Josiah, 1855-1916 (Book collections on Project MUSE., 2009)
Josiah Royce is one of the central figures in American philosophy. This reprint of Royce's 1908 book includes, in addition to the five original essays, a collection of six additional essays by Royce added by the editors which complement and expand upon the thought of the initial volume.